The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.5194/acp-10-7669-2010
|View full text |Cite
|
Sign up to set email alerts
|

Cloud albedo increase from carbonaceous aerosol

Abstract: Abstract. Airborne measurements from two consecutive days, analysed with the aid of an aerosol-adiabatic cloud parcel model, are used to study the effect of carbonaceous aerosol particles on the reflectivity of sunlight by water clouds. The measurements, including aerosol chemistry, aerosol microphysics, cloud microphysics, cloud gust velocities and cloud light extinction, were made below, in and above stratocumulus over the northwest Atlantic Ocean. On the first day, the history of the below-cloud fine partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 74 publications
0
30
0
Order By: Relevance
“…They had suggested that one explanation could have been that the mechanism for SOA formation was more efficient than assumed. Leaitch et al (2010) conducted flights in October 2003 off the Nova Scotia coast as part of the Canadian Surface Ocean-Lower Atmosphere Study (SOLAS). This was an important study as it was perhaps the first airborne effort up until that time to probe ACI.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 99%
See 1 more Smart Citation
“…They had suggested that one explanation could have been that the mechanism for SOA formation was more efficient than assumed. Leaitch et al (2010) conducted flights in October 2003 off the Nova Scotia coast as part of the Canadian Surface Ocean-Lower Atmosphere Study (SOLAS). This was an important study as it was perhaps the first airborne effort up until that time to probe ACI.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 99%
“…With regard to past WNAO studies of how aerosols affect clouds, two airborne investigations as part of NARE (Leaitch et al, 1996) and SOLAS (Leaitch et al, 2010) specifically focused on N d and controlling factors such as degree of turbulence and abundance of carbonaceous aerosol. Medina et al (2007) conducted a surface-based CCN closure study at the Thompson Farm AIRMAP site in New Hampshire and concluded that size-resolved chemical data and treatment of mixing state are helpful for more successful closure.…”
Section: Aerosol-cloud Interactionsmentioning
confidence: 99%
“…These studies have investigated the influences of aerosol physical properties (number concentration and size distribution), chemical properties (chemical composition and hygroscopicity), and the above mentioned effects of organics on cloud properties (cloud droplet number concentration and indirect radiative forcing). Some studies have shown that the influences of chemical properties of aerosol particles and the effects of organics on the cloud activation are particularly significant in polluted environments [Lance et al, 2004;Leaitch et al, 2010]. In contrast, other studies have shown that the effects of aerosol physical properties are important and that the effects of chemical properties and organics are small [Fountoukis et al, 2007;Reutter et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…The size distribution and chemical composition of aerosol particles are the preeminent factors dictating CCN ability. The relative importance of these factors is not clear, as previous studies have demonstrated both size and composition as the predominant factors controlling CCN ability [ Dusek et al , 2006; Leaitch et al , 2010; Quinn et al , 2008; Zelenyuk et al , 2010]. The mixing state of aerosol can also play a role; however, the distinction between internally and externally mixed particles as CCN becomes less significant if particles are sufficiently hygroscopic [ Wang et al , 2010].…”
Section: Introductionmentioning
confidence: 99%